PRIORITIES OF REALIZATION OF MEDICAL TECHNOLOGIES IN A DENTAL POLYCLINIC - Анатолий Иванович Бабенко; Наталья Викторовна Кузнецова; Евгений Анатольевич Бабенко (Медицина в Кузбассе)
Objective – to establish the priorities and a specific gravity of a significance of demand of separate types of the dental technologies for the adult population realized in the territorial dental polyclinic.